(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2005)
A histological study was conducted on 100 subjects of both sexes (M-50, F-50) from the compact portion of the tibia to observe changes related to age in the lamellae per osteon, in the haversion system in human compact bone. In majority of cases it was observed that the number of lamellae was found to be 6 to 10 per osteon from 18 to 55 yrs. of age. After 55 yrs. of age, 3 to 4 lamellae were seen, per osteon.